ARTEMISIA: ARTEMISININ METABOLISM AND METABOLOMICS - Meyer, M.; Hussein, A.; Muranaka, T.; Seki, H.; vd Kooy, F.; Verpoorte, R. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Artemisia annua has a long history of use in traditional Chinese medicine. We determined that A. afra, a well-known indigenous South African medicinal plant does not synthesise artemisinin. It does however produce several other terpenoids including sesquiterpenes. We performed comparative molecular genomics and metabolomics studies between A. annua and A. afra and succeeded to profile their terpenes and the genes involved in their biosyntheses. Two enzymes 1) amorpha-4,11-diene synthase (ADS), catalysing the first regulating step leading to artemisinin, and 2) CYP71AV1, oxidising amorpha-4,11-diene to produce artemisinic acid (one of biosynthetic intermediates for artemisinin), have previously been shown to be involved in the biosynthesis of artemisinin in A. annua. We determined that the gene for CYP71AV1 is expressed but that the ADS gene is not, in A. afra. A transgenic system was established for A. afra and transgenic plants have been created, we will report on these results. Our goal in this project was to create an artemisinin-producing A. afra for a sustainable supply of the drug. We will also report on the results of a metabolomic quality control analysis of A. afra, A. annua and tablets of A. afra used in the prevention of malaria.